OBSERVATIONS ON THE MATURITY AND SPAWNING OF METAPENAEUS MONOCEROS (FABRICIUS) AT COCHIN - Nalini, C (Indian Journal of Fisheries, 2011)
Among the penaeid prawns constituting the commercial prawn fishery of India, Metapenaeus monoceros (Fabricius), locally called "Choodan chemmeen" (Malayalam), forms an important species accounting for nearly 10% of the total marine prawn landings of the country (Mohamed 1967). The species also contributes to a substantial portion of the prawn catches from the estuaries and backwaters all along the coast and is cultured extensively in the low-lying brackishwater fields in the coastal areas